Respon Ganda Elektrode Kawat Emas Terlapis Polipirol Terhadap Kation Dan Anion Dari Surfaktan Nads - Watoni, Abdul Haris (Universitas Halu Oleo, 2011)
The coating of gold wire electrode as working electrode with polypyrrole throughelectropolymerization by ciclyc voltammetry was performanced in the 0.01 M pyrrole solutioncontaining 1,0 ´ 10-4 M HDS dopant and 0.01 M KCl, KBr, and KI supporting electrolytes,respectively. The coated electrode prepared by KCl supporting electrolyte has the respontoward Na+ cations with highest sensitivity of 44.0 mV/decade in the concentration range of5,0 ´ 10-5 – 1,0 ´ 10-3 M and toward DS- anions with highest sensitivity of 26.2 mV/decadein the concentration range of 1,0 ´ 10-15 – 1,0 ´ 10-12 M. Coated electrode prepared by KBrsupporting electrolyte might respon toward Na+ cations with highest sensitivity of 42.4mV/decade in the concentration range of 5,0 ´ 10-4 – 1,0 ´ 10-3 M and toward DS- anionswith highest sensitivity of 35.0 mV/decade. The coated electrode prepared by KI supprotingelectrolyte has a respon toward Na+ cations with highest sensitivity of 49.2 mV/decade in theconcentration range of 5,0 ´ 10-4 – 1,0 ´ 10-3 M and toward DS- anions with highestsensitivity of 16.5 mV/decade in the concentration range of 1,0 ´ 10-15 – 1,0 ´ 10-9 M.